Effect of Herbicides and Azotobacter chroococcum Bacteria on Soil Bacterial Growth, Growth, and Yield of Maize (Zea mays L.) - M. Abd, Zainab; Hasan, Alaa E. (Journal of Tropical Crop Science, 2026)
To obtain high yield, herbicides are applied to food crops, including maize. It is important to adopt sustainable agricultural practices to enhance soil fertility by bacterial inoculation. Two experiments were conducted at the Faculty of Agriculture, University of Kufa, Iraq, to investigate the effects of glyphosate and 2,4 D herbicides on soil bacterial activity, growth, and maize (Zea mays L.) yield. A laboratory experiment, using a completely randomized design, evaluated the response of Azotobacter chroococcum and Bacillus subtilis to varying herbicide concentrations. Bacterial populations were quantified after 24 hr of incubation to determine the minimum inhibitory concentration within the nutrient medium. Subsequently, a f ield experiment was conducted in a sandy loam soil during the 2024–2025 autumn season using a randomized complete block design; the factors included bacterial inoculation and herbicide application at three rates: half, full (recommended), and double the recommended dose. Results indicated that high concentrations of glyphosate and 2,4-D significantly reduced total bacterial counts to 3.50 × 10⁶ CFU/g dry soil. Conversely, inoculation with A. chroococcum increased the population to 18.83 × 10⁶ CFU/g, with the interaction between A. chroococcum and the recommended glyphosate dose achieving the highest density of 37.00 × 10⁶ CFU/g. Regarding plant physiology, inoculation increased total chlorophyll content from 1.33 to 1.68 mg/g and leaf area from 415.34 to 879.71 cm2 per plant. Leaf nutrient concentrations also improved significantly; nitrogen rose from 1.18% to 2.08%, phosphorus from 0.17% to 0.23%, and potassium from 1.26% to 1.50%. These improvements were reflected in vegetative growth and productivity; the dry weight of the vegetative system increased from 199.25 g in uninoculated controls to 278.36 g in the full-recommended glyphosate treatment with inoculation. Total grain yield ranged from 12.31 to 16.29 t/ha, with A. chroococcum inoculation alone reaching a mean yield of 15.57 t/ha.